PENGARUH KINERJA DOSEN, FASILITAS DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN MAHASISWA STMIK AMIKOM PURWOKERTO - Lusi Suwandari (JBIMA (Jurnal Bisnis dan Manajemen), 2013)
Student satisfaction is a critical measure in the success of higher education institutions that aim at retaining students until graduation. This study examines the factors which influence student satisfaction in the following order: lecture performance, organization facilities and organizational commitment. The findings reveal that organizational commitment is directly a positively affected by the dimension that determines satisfaction. Based on the path coefficient, proportional and t- calculated value for each variable, the organizational commitment have a higher influence than the lecture performance and organization facilities variable to students satisfaction.